Enhancing the sustainability of cowpea production through the integrated use of fish effluents and animal manure - Andre A. Diatta; César Bassène; Anicet G. B. Manga; Yolande Senghor; Mariama Sambou; Cheikh Mbow (Agrosystems, Geosciences & Environment)
Abstract The integration of aquaculture and agriculture in arid and semi‐arid environments is crucial for maximizing water and land productivity, especially considering the increasing global water scarcity and the simultaneous use of water for crop and fish production. A greenhouse study was conducted to determine the effects of fish effluent on the growth, yield parameters, and yield of cowpea (Vigna unguiculata). The experiment involved 13 fertilization treatments, including three types of irrigation water (river water—control, Nile tilapia (Oreochromis niloticus), African sharp‐toothed catfish (Clarias gariepinus), four fertilizers (poultry, cattle, and sheep manures at 10 t ha−1), recommended rate of inorganic fertilizer (150 kg ha−1 of NPK 6‐20‐10), and six mixed treatments with fish effluent and 50% of the applied rate of manure alone (5 t ha−1). The combined use of C. gariepinus effluent + 50% poultry manure significantly increased stem diameter, nodules per plant, pods per plant, and seed yield compared to NPK treatments. The shortest days to reach 50% flowering were obtained with the effluent of O. niloticus + 50% sheep manure, C. gariepinus/O. niloticus + 50% poultry manure, and 10 t ha−1 poultry manure. However, fertilization treatments did not significantly influence the number of branches, pod and root length, number of pods per plant, 100‐seed weight, and leaf chlorophyll concentrations. This study suggests that fish effluents, when combined with manure, can improve plant growth and seed yield, providing a cost‐effective alternative to inorganic fertilizers for smallholder farmers.